The effect of online collaborative writing instruction on enhancing writing performance, writing motivation, and writing self-efficacy of Chinese EFL learners - Yan Li (Frontiers in Psychology, 2023)
IntroductionThis study investigates the influence of online collaborative writing instruction on the writing performance, writing self-efficacy, and writing motivation of Chinese English as a foreign language (EFL) learners. The research was conducted at a language school in mainland China with 58 participants divided into an experimental group (n=30) and a control group (n=28).MethodsThe experimental group utilized Tencent Docs, an online platform, for collaborative writing and peer-editing activities outside the classroom, while the control group received traditional in-class instruction. The study spanned a duration of 13 weeks, during which writing tasks, writing motivation scales, and writing self-efficacy scales were employed to collect data.ResultsThe findings revealed that the experimental group exhibited significantly greater improvement in writing performance, motivation, and self-efficacy compared to the control group. These results indicate the positive impact of incorporating Tencent Docs into collaborative writing instruction.DiscussionThe outcomes of this study provide valuable insights for language educators regarding the benefits of integrating online tools into EFL instruction to enhance writing skills. By leveraging platforms like Tencent Docs for collaborative writing, instructors can foster improved performance, increased motivation, and enhanced self-efficacy among EFL learners. Overall, this research highlights the effectiveness of online collaborative writing instruction and its potential as a valuable tool for language educators seeking to optimize EFL learners’ writing abilities.